ANALISIS FINANSIAL USAHATANI CABAI RAWIT (Capsicum frutescens L) DI DESA PURWAJAYA KECAMATAN LOA JANAN - Husni, Abdul Kholik Hidayah, dan Maskan AF (Universitas 17 Agustus 1945 Samarinda, 2014)
This study aims to analyze the financial of chili farming. This research was conducted in the village of Purwajaya, Loa Janan sub district, Kutai Kartanegara Regency began in February 2013 until April 2013. research will be undertaken include census data retrieval biographical data of respondents, quisoner and interviews in the study site, the number of farmer respondents were 11 people. The data used in this study is primary data and secondary data. Chili farming conditions in the village Purwajaya showed good results in the amount of 13.522,71 kgs/ha. The results showed that the average income of respondents was Rp.162.272.463,77,-/ha and the expenditure of Rp.78.251.032,90,-/ha so that the income of Rp.84.021.430.87,-/ha. This means that the level of efficiency of agricultural production chili 2.07 ratio calculation. Value of BEP (Break-even point) for volume production at 5.786,64 kgs/ha and BEP production price Rp.6520,9,-/kgs which means that it is very efficient for chili farming in manage (favorable) or with the addition of Rp 1.00 expenses will generating revenue of 2.07.